Hunger in vulnerable families in Southeastern Europe: Associations with mental health and violence - Jansen, E; Lachman, JM; Heinrichs, N; Hutchings, J; Baban, A; Foran, HM (Frontiers Media, 2020)
Background: Hunger can influence healthy development of children and has been shown to be associated with other determinants of child health, such as violence within the family and maternal (mental) health problems. Whilst the majority of research has been conducted in high-income countries with vulnerable populations, less is known about the circumstances in low-and-middle-income countries. This study explored the experience of hunger in vulnerable families in three Southeastern European countries, and simultaneously examined relationships with four sets of risk factors—lack of financial, mental, familial, and social resources.